PENINGKATAN KUALITAS LAYANAN KEPADA PELANGGAN DI TERMINAL PENUMPANG PELABUHAN TANJUNG PERAK SURABAYA - Hariastuti, Ni Luh Putu; Ardiansyah, Dwi Rifki (Jurnal Ilmiah Teknik Industri, 2013)
To be able to retain its customer, PT Pelindo III Tanjung Perak Surabaya must serve and fulfill what is desired by prospective passengers so that they can maintain the loyalty of passengers who use the services. In this observation, there are 6 criterias that have servqual value below the average values (-0.03746). The first criteria is, the capacity of the waiting room (seats) is adequate (-0.16206), comfortable waiting room (-0.1500), security of luggage passengers (-0.08232), hygiene at Tanjung Perak harbor (-0.06160), giving attention to the grievances of passengers (-0.05896), and management responsiveness to complaints of passengers (-0.05040). This indicates that the port services are still not able to fulfill customer expectations. Method to solve this problem is using the TRIZ method. Results obtained from the analysis using TRIZ,that acquired  4 solutions given to the manager. The 4 solutions are division of task should be differentiated according to the places that exist in the passenger terminal, the process of measuring the quality of services they provide in a regularly and periodically, changes in physical conditions, especially the addition of a seat and air conditioning (central) or fan.